The high-power pulsed beams source with tunable operation mode; Energy Fluxes and Radiation Effects (EFRE-2016) - Nashilevskiy A. V. Aleksandr Vladimirovich; Kanaev G. G. Gennady Grigorevich; Ezhov V. V. Vitali Vladimirovich; Shamanin V. I. Vitaly Igorevich; Remnev G. E. Gennady Efimovich (2016, 2016)
Title screen